Евгений Онегин - Пушкин Александр Сергеевич (Всемирная литература, 2019)
Экземпляры: СБ (20191209) / Инвентарный номер: 58742 / Цена: 102.00 / Сис.шифр: Р1 / Авт.знак: П 91 / ГРНТИ: 17.82.10 / ББК: 84(2Рос=Рус)1